Perioperative blood product transfusion of two different perfusion strategies on pediatric patients undergoing aortic arch surgery. Issue 1 (5th August 2019) - Tong, Yuanyuan; Zhang, Peiyao; Li, Shoujun; Yan, Jun; Feng, Zhengyi; Zhao, Ju; Guo, Shengwen; Jin, Yu; Liu, Jinping
Abstract: Simple regional cerebral perfusion (SRCP) or cerebro‐myocardial perfusion (CMP) is selectively used in one‐stage complex aortic arch malformation repair. This analysis was performed to investigate the effect of CMP and SRCP on perioperative blood product consumption, and to evaluate whether these two strategies have different effects on the clinical outcomes. A retrospective analysis of 284 children with complicated aortic malformation from January 2010 to June 2018 was performed. The overall cohort was divided into SRCP group ( n = 202) and CMP group ( n = 82). A comprehensive comparison of perioperative blood product consumption‐related indexes was performed. Cardiopulmonary bypass time, cardiac arrest time, cooling, and rewarming time in the CMP group were significantly shorter than those in the SRCP group ( P < .05). Chest tube time was 3.82 ± 1.33 days in the SRCP group compared to 3.42 ± 0.97 days in the CMP group ( P = .005). Moreover, intraoperative platelet (PLT) transfusion volume (mL/kg) and rate (%) were significantly lower in the CMP group ( P < .001). Multivariate regression analysis found that intraoperative PLT transfusion was significantly negatively correlated with CMP management [OR = 0.237 (0.110‐0.507), P < .001] and CPB time was independently associated with delayed chest tube removal (>3 days) [OR = 1.010 (1.001‐1.020), P = .031]. In‐hospital mortality and early postoperative adverse events were not significantly different between the two groups. In children with on‐pump complex aortic arch surgeries, CMP is more preferable than SRCP in blood protection. However, overall prognosis was not remarkably different between these two perfusion groups. They are both safe and feasible.